1994
DOI: 10.1046/j.1471-4159.1994.63020570.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Expression of Opioid and σ Receptors in Rat C6 Glioma and Mouse N18TG2 Neuroblastoma Cells

Abstract: Mouse N18TG2 neuroblastoma and rat C6 glioma cell lines were injected into male nude mice, and the tumors were passaged serially. At each generation, tumors were analyzed for δ opioid binding using [3H][d‐Ala2,d‐Leu5]enkephalin and for σ1 and σ2 binding with 1,3‐[3H]di‐o‐tolylguanidine in the presence and absence of 1 µM pentazocine. Receptor density (Bmax) and affinity (KD) were estimated by homologous competition binding assays. Opioid and σBmax values in the solid tumors were significantly lower than their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Sigma-2 receptor expression has been reported in various human cancer cells such as breast[19], brain[20], bladder[21], colon and melanoma[22]; however, no studies have been reported on sigma-2 receptor expression in pancreas adenocarcinoma. Sigma-2 receptor-specific ligands have been found to induce apoptosis [19-22], raising the possibility that these ligands can act as sensitizers to standard chemotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…Sigma-2 receptor expression has been reported in various human cancer cells such as breast[19], brain[20], bladder[21], colon and melanoma[22]; however, no studies have been reported on sigma-2 receptor expression in pancreas adenocarcinoma. Sigma-2 receptor-specific ligands have been found to induce apoptosis [19-22], raising the possibility that these ligands can act as sensitizers to standard chemotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…Sigma-2 receptors are up-regulated in many cancer types [39, 40] and SMAC mimetics have been shown to sensitize many types of cancer to a wide array of chemotherapeutic agents [17, 41, 42]. As a result, we believe that SW IV-134 could potentially be used to sensitize several additional sigma-2-expressing malignancies, including head and neck tumors, breast cancer, lymphomas [43], and ovarian cancer [22] to different chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…For the sigma-1 receptor specifically, as examples these include cancers of the breast (except MCF-7 cells), lung (small cell and non-small cell lung cancer cells), colon, ovaries and prostate (androgen dependent and androgen independent cancers) and brain [28,118,[302][303][304][305][306][307][308] . The reported Bmax range for these cancer cell lines is 180 -6839 fmol/mg protein (most are well above 1000 fmol/mg protein), including those of rodent and human origin.…”
Section: Sigma-1 Receptors As Tumor Associated Markersmentioning
confidence: 99%